2021
DOI: 10.1101/2021.05.27.446072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cell cycle-dependent GARP-like transcriptional repressor regulates the initiation of differentiation in Giardia lamblia

Abstract: Transcriptional regulation of differentiation is critical for parasitic pathogens to adapt to environmental changes and regulate transmission. How early signaling transcription factors (TF) activate signal transduction to initiate encystation remains an open question in Giardia. Here, we generate a CasRX-mediated knockdown system, together with an established CRISPRi system to screen early signaling TFs in Giardia lamblia. We identified an early response TF, GARP4 that regulates cyst wall protein (CWP) levels … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…Therefore, the natural tetraploidy of G. intestinalis in combination with incomplete removal of gene alleles by CRISPR/Cas9 provides an experimental way to suppress gene expression by manipulation with gene dose. These data showed that CRISPR/Cas9 may actually represent an alternative strategy to CRISPRi [ 23 ] and CasRx [ 24 ] for gene silencing in G. intestinalis .
Figure 7 CRISPR/Cas9-mediated knockdown of tom40 .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the natural tetraploidy of G. intestinalis in combination with incomplete removal of gene alleles by CRISPR/Cas9 provides an experimental way to suppress gene expression by manipulation with gene dose. These data showed that CRISPR/Cas9 may actually represent an alternative strategy to CRISPRi [ 23 ] and CasRx [ 24 ] for gene silencing in G. intestinalis .
Figure 7 CRISPR/Cas9-mediated knockdown of tom40 .
…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22]. Recently, the catalytically inactive form of the CRISPR/Cas9 system, CRISPRi, has been introduced to G. intestinalis for the successful knockdown of several genes that encode cytoskeletal proteins [23] and recently, RNA-targeting Cas ribonuclease, CasRx, was experimentally used in G. intestinalis [24]. The 'classical' CRISPR/Cas9 approach was used to reduce the gene expression in G. intestinalis [25,26] but this strategy did not achieve full genomic knockout.…”
Section: Introductionmentioning
confidence: 99%